Tracing the Origins of IgE, Mast Cells, and Allergies by Studies of Wild Animals - Hellman, Lars Torkel; Akula, Srinivas; Thorpe, Michael; Fu, Zhirong (Frontiers in Immunology, 2017)
In most industrialized countries allergies have increased in frequency quite dramatically during the past 50 years. Estimates show that 20-30% of the populations are affected. Allergies have thereby become one of the major medical challenges of the 21st century. Despite several theories including the hygiene hypothesis there are still very few solid clues concerning the causes of this increase. To trace the origins of allergies we have studied cells and molecules of importance for the development of IgE mediated allergies, including when they have appeared during vertebrate evolution. By studying the immunoglobulin repertoire in the three extant mammalian lineages we have been able to show that IgE and IgG most likely appeared by a gene duplication of IgY in an early mammal, possibly 220-300 million years ago. Receptors specific for IgE and IgG subsequently appeared in parallel with the increase in Ig isotypes from a subfamily of the recently identified Fc receptor-like molecules. Circulating IgE levels are generally very low in humans and laboratory rodents. However, when dogs and Scandinavian wolfs were analyzed, IgE levels were found to be 100-200 times higher compared to humans, indicating a generally much more active IgE synthesis in free-living animals, most likely connected to intestinal parasite infections. One of the major effector molecules released upon IgE-mediated activation by mast cells are serine proteases. These proteases, which belong to the large family of hematopoietic serine proteases, are extremely abundant and can account for up to 35% of the total cellular protein. Recent studies show that several of these enzymes, including the chymases and tryptases, have been part of the mast cell granule repertoire for more than 200 million years. The first members of the larger family of hematopoietic serine proteases seemed to have appeared with the jawed vertebrates. The aim is now to continue these studies of mast cell biology and IgE to obtain additional clues to their evolutionary conserved functions. A focus concerns why the humoral immune response involving IgE and mast cells have become so dysregulated in humans as well as several of our domestic companion animals.